QRIS Adoption Among Students is Reviewed from Financial Literacy, Digital Literacy, and Information Security - Setiana Siti Humayroh; Riawan .; Titi Rapini (Program Studi Akuntansi FPEB UPI, 2024)
Technological developments are now penetrating the financial sector, one of which is the payment system. Bank Indonesia has launched a standardized QR code, namely QRIS, whose users have increased significantly since it was first launched. However, amidst the high number of QRIS users, it turns out there are still some who don't know and use this payment technology. The aim of this research is to find out whether financial literacy, digital literacy and information security influence the decision to use QRIS among students at Muhammadiyah University of Ponorogo. This research is included in quantitative research. The population in this study were students at Muhammadiyah University of Ponorogo who used QRIS. The sample in the study was selected using a purposive sampling method and 128 respondents were obtained who met the sample criteria. Empirical data was collected from questionnaires distributed via Google Form, then analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The research results show that there is a significant influence between the variables financial literacy, digital literacy, and information security on the decision to use QRIS among Muhammadiyah University Ponorogo students.